A Detailed Comparative Study of RBF Well Yield and River Flow - H. Vijaya Kumar; Nagraj S. Pati (New Ideas Concerning Science and Technology Vol. 6, 2021)
Nontoxic drinking water is necessary for all life forms even though it offers no calories or organic nutrients. Nontoxic water sources are getting scarcer and contamination of these sources is growing due to excess extraction from available sources to meet the growing water demand and inadequate sanitation facilities establishment. Although the approach to nontoxic drinking water has improved over the last few decades in almost every part of the world, approximately one billion people remain deprived of safe water, and over 2.5 billion lack access to adequate sanitation. Riverbank filtration is a natural water purification technology that extracts river water via wells located on the riverbank. This work compares the production well yield with a river flow. Pumping test was carried out for determining yield of a production well at a small village named somlapura on the bank of Tungabhadra River, Karnataka, India. The river discharge obtained from the Water Commission Board was compared to the yield of the River bank well measured by water metre (Davangere). Even though the river flow varies, the results show that the well yield remains constant during the observation period. Hence, it is concluded that, the RBF well yields the water at the rate of 330 liters/minute. Average Production of water from a well is 0.48 MLD (million liters per day). Therefore, with this production rate it can serve population of three thousand five hundred fifty five with 135 LPCD (liters per capita per day).